Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.socscimed.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Gender, stress in childhood and adulthood, and trajectories of change in body mass

Abstract: Despite substantial evidence of the linkage between stress and weight change, previous studies have not considered how stress trajectories that begin in childhood and fluctuate throughout adulthood may work together to have long-term consequences for weight change. Working from a stress and life course perspective, we investigate the linkages between childhood stress, adulthood stress and trajectories of change in body mass (i.e., Body Mass Index, BMI) over time, with attention to possible gender variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 72 publications
3
26
1
Order By: Relevance
“…These alterations have been often linked to the early life dysregulation of the sympathetic nerve activity (SNA) and/or the HPA axis 5254 . Despite most of these studies have not been designed to test sex-specific effects on the cardiovascular and metabolic risk, a growing body of evidence shows that long-term effects of ELS may impact women’s susceptibility to gain weight and develop insulin resistance at a greater fashion 23,5557 ; however, the potential origins for this predisposition remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These alterations have been often linked to the early life dysregulation of the sympathetic nerve activity (SNA) and/or the HPA axis 5254 . Despite most of these studies have not been designed to test sex-specific effects on the cardiovascular and metabolic risk, a growing body of evidence shows that long-term effects of ELS may impact women’s susceptibility to gain weight and develop insulin resistance at a greater fashion 23,5557 ; however, the potential origins for this predisposition remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies identified the exposure to all these forms of early life stress (ELS) as an independent risk factor for type 2 diabetes and ischemic heart disease, in part by increasing body mass index (BMI) and systolic blood pressure (SBP) 811 . Findings from the Georgia Stress and Heart Study (GSH) including 213 African Americans and 181 European Americans, revealed that individuals exposed to multiple ELS factors display a greater increase in blood pressure (BP) levels compared to control individuals in a 23-year follow up period 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight gain was detected extremely early in pregnancy. Liu and Umberson [29] found that children who experience more stress subsequently experience more stress as adults. Women have higher BMI than men.…”
Section: Discussionmentioning
confidence: 99%
“…Early-life adversity, such as trauma or maltreatment, can exert a “long shadow” (Brent & Silverstein, 2013), that is, a profound and, thus, long-lasting impact on the affected individual (Liu & Umberson, 2015; Springer, Sheridan, Kuo, & Carnes, 2003; Umberson, Williams, Powers, Liu, & Needham, 2005). The World Health Organization (WHO), which conducted a worldwide survey including over 50,000 respondents, concluded that childhood adversities are strongly associated with adult mental disorders and are found to predict 29.8% of DSM-IV disorders (Kessler et al, 2010).…”
mentioning
confidence: 99%